The Analysis of Instrument Quality to Measure Graduate Students’ Higher Order Thinking Skill in Environmental Education Learning - Wihardjo, R. Sihadi Darmo; Muktiono, Ayub; Ramadhan, Syahrul; Salman, Ibnu; Hadiana, Deni (International Journal of Membrane Science and Technology, 2023)
This research aims to develop a valid and reliable assessment instrument for measuring students' Higher Order Thinking Skills (HOTS) in environmental education learning. The study follows a research and development design, adapted from the development model proposed by Borg and Gall. The researcher modified the original model into several stages, including (1) gathering information, (2) making a plan, (3) preparing the product form, (4) conducting revisions of the initial product, and (5) implementing the final product. The trial subjects for this research consisted of 34 graduate students enrolled in the Population and Environmental Education Study Program at Jakarta State University. Data collection involved administering a test comprising 20 multiple-choice items related to environmental education learning, specifically focusing on HOTS. The QUEST program was utilized to analyze the collected data, examining the validity, reliability, difficulty level, and question differentiator of the assessment instrument. The results of this research demonstrate the successful development of a feasible assessment instrument for measuring graduate students' HOTS. The instrument exhibits high validity and reliability, ensuring that it accurately measures the targeted higher-order thinking skills. Moreover, the difficulty level and question differentiator of the items are well-balanced, allowing for effective differentiation among students' thinking abilities. This assessment instrument holds significant potential as an alternative tool for evaluating graduate students' HOTS in environmental education learning. It provides educators with a reliable means to assess and monitor students' higher-order thinking abilities, enabling the identification of areas that require further development. By incorporating this instrument into the assessment process, educators can facilitate the cultivation of critical thinking, problem-solving, and creativity skills among graduate students.